Breeding better banana montage - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
This unique project seeks to improve the production and productivity of banana in Tanzania and Uganda, through the development of hybrid banana varieties that are expected to have 30% higher yield compared to the current varieties grown by farmers under the same conditions. In particular, the project will strengthen the banana breeding programs in the two countries, towards developing new high-yielding hybrid banana varieties with resistance to key pests and diseases. The project is focused primarily on building an efficient breeding platform for banana and improving the two most popular cooking bananas in the region: East Africa highland banana (EAHB), also known as Matooke, and Mchare, fortifying resistance against pests and diseases but maintaining the traits enjoyed by consumers.